Synthesis of novel oligomeric anionic alkyl glycosides using laccase/TEMPO oxidation and cyclodextrin glucanotransferase (CGTase)‐catalyzed transglycosylation. Issue 7 (3rd May 2021) - Ngo, Ngoc T. N.; Linares‐Pastén, Javier A.; Grey, Carl; Adlercreutz, Patrick
Abstract: Modification of alkyl glycosides, to alter their properties and widen the scope of potential applications, is of considerable interest. Here, we report the synthesis of new anionic alkyl glycosides with long carbohydrate chains, using two different approaches: laccase/2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO) oxidation of a long‐carbohydrate‐chain alkyl glycoside and cyclodextrin glucanotransferase (CGTase)‐catalyzed elongation of anionic alkyl glycosides. The laccase/TEMPO oxidation of dodecyl β‐ d ‐maltooctaoside proceeded efficiently with the formation of aldehyde and acid products. However, depolymerization occurred to a large extent, limiting the product yield and purity. On the other hand, CGTase‐catalyzed coupling/disproportionation reactions with α‐cyclodextrin and dodecyl β‐ d ‐maltoside diuronic acid (DDM‐2COOH) or octyl β‐ d ‐glucuronic acid (OG‐COOH) as substrates gave high conversions, especially when the CGTase Toruzyme was used. It was found that pH had a strong influence on both the enzyme activity and the acceptor specificity. With non‐ionic substrates (dodecyl β‐ d ‐maltoside and octyl β‐ d ‐glucoside), Toruzyme exhibited high catalytic activity at pH 5–6, but for the acidic substrates (DDM‐2COOH and OG‐COOH) the activity was highest at pH 4. This is most likely due to the enzyme favoring the protonated forms of DDM‐2COOH and OG‐COOH, which exist at lower pH (pKa about 3). Abstract : Alkyl glycoside surfactants having long carbohydrate groups including carboxyl groups were synthesized. The carboxyl groups were introduced by chemoenzymatic oxidation and the elongation of the carbohydrate groups was achieved using cyclodextrin glucanotransferase (CGTase) as catalyst. The ability of the CGTase to accept carboxyl containing substrates was studied both experimentally and using molecular modelling.